Wind power coating as well as preparation method and application thereof
By using flake glass, composite oxide, phenolic epoxy resin and hydroxyl-terminated polyurethane resin in wind power coatings, and controlling the Ce3+ content and using an anhydride curing agent and cationic curing agent, the shortcomings of wind power coatings in weather resistance, corrosion resistance and adaptability are solved, and higher durability and environmental protection performance are achieved.
Patent Information
- Application Number
- CN202411988634.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
Existing wind power coatings have shortcomings in weather resistance, corrosion resistance and adaptability, and have a great impact on the environment.
A wind-electric coating including scale glass, composite oxide, phenolic epoxy resin and hydroxyl-terminated polyurethane resin is used to improve the durability and stability of the coating by controlling the content of Ce3+ in the composite oxide and using a combination of an anhydride curing agent and a cationic curing agent.
It significantly improves the weather resistance, corrosion resistance and adaptability of wind power coatings, extends the service life of the equipment, and reduces environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of wind power, and in particular to a wind power coating and a preparation method and application thereof. Background Art
[0002] Wind power coating is a special coating specially used for surface coating of wind power equipment (such as wind power blades, wind power towers, etc.), which aims to improve the equipment's weather resistance, corrosion resistance, wear resistance, wind and sand resistance, stone impact resistance and other performance, thereby extending the service life of the equipment and ensuring its safe and stable operation. At present, wind power coating is widely used in various fields of wind power equipment. For example, wind power blades, as one of the key components of wind power equipment, the surface coating of wind power blades is crucial to protect the blades from erosion by the natural environment. Another example is the wind power tower. The wind power tower is the main structure that supports the wind power blades and generators, and its anti-corrosion coating should not be ignored. And other wind power equipment, such as wind power foundations, transformers, control cabinets and other auxiliary equipment also need to be coated and protected.
[0003] There are many types of wind power coatings, mainly including polyurethane coatings, epoxy coatings, fluorocarbon coatings, graphene anti-corrosion coatings and flake anti-corrosion coatings. Wind power coatings usually need to have high weather resistance and be able to resist the erosion of wind power equipment by extreme weather conditions (such as strong winds, severe cold, and extreme heat). It has strong corrosion resistance and can effectively prevent environmental factors such as salt spray and humidity from corroding the equipment, extending the service life of the equipment. It must also be wear-resistant and able to resist mechanical wear such as wind, sand, and stone strikes, protecting the surface of the equipment from damage. To a certain extent, it should also be environmentally friendly. More and more wind power coatings use environmentally friendly raw materials and production processes to reduce pollution to the environment.
[0004] In order to solve the above problems, it is urgent to develop new wind power coatings to enhance their weather resistance, corrosion resistance and adaptability while reducing environmental impact. Summary of the invention
[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a wind power coating and a preparation method and application thereof to solve the problems of poor weather resistance, corrosion resistance and adaptability.
[0006] To achieve the above objectives, the first aspect of the present invention provides a wind power coating, which includes component I and component II; wherein component I includes flake glass, composite oxide, phenolic epoxy resin, hydroxyl-terminated polyurethane resin and antioxidant, wherein the composite oxide includes rod-shaped titanium dioxide and cerium oxide, and Ce in the composite oxide is 3+ The content of Ce in the composite oxide is 25-35% by weight of the total cerium content; the component II includes a curing agent. 3+The content of Ce can be controlled, but not limited to, at 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt% and the like, accounting for the total cerium content. For another example, in the present invention, Ce in the composite oxide is 3+ The content of cerium can be, but is not limited to, controlled at 25-35 wt %, 28-32 wt %, etc. of the total cerium content.
[0007] On the basis of the above technical solution, based on the total weight of the composite oxide, the content of rod-shaped titanium dioxide is 70-95% by weight, and the content of cerium oxide is 5-30% by weight.
[0008] Based on the above technical solution, the aspect ratio of the rod-shaped titanium dioxide is 2-10: 1. The aspect ratio of the rod-shaped titanium dioxide is, for example but not limited to, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc.
[0009] Based on the above technical solution, the thickness-to-diameter ratio of the flake glass is greater than 40 μm, preferably 70-90 μm.
[0010] Based on the above technical solution, the thickness of the flake glass is 3-7 μm.
[0011] Based on the above technical solution, the diameter of the flake glass is 40-150 μm. In the present invention, for the aspect ratio, thickness and diameter of the flake glass, within the above preferred range, the overall performance of the coating is better.
[0012] On the basis of the above technical solution, based on the total weight of the flake glass, the flake glass contains 50-80 weight % of SiO2, 5-10 weight % of Al2O3, 8-15 weight % of CaO, 2-8 weight % of MgO, 5-20 weight % of Na2O+K2O, and 0-0.5 weight % of Fe2O3.
[0013] On the basis of the above technical scheme, based on the total weight of component I, the content of flake glass is 30-40 weight%, the content of composite oxide is 5-20 weight%, the content of phenolic epoxy resin is 20-40 weight%, the content of hydroxyl-terminated polyurethane resin is 20-30 weight%, and the content of antioxidant is 5-10 weight%.
[0014] On the basis of the above technical solution, the phenolic epoxy resin may be but is not limited to phenolic epoxy resin F51.
[0015] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.
[0016] On the basis of the above technical solution, the curing agent includes anhydride curing agent and a cationic curing agent.
[0017] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.
[0018] On the basis of the above technical solution, the cationic curing agent is selected from one or more of ammonium salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, boron trifluoride ether complex, etc.
[0019] On the basis of the above technical solution, the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6. The weight ratio of the anhydride curing agent to the cationic curing agent is, for example but not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6.
[0020] On the basis of the above technical solution, the weight ratio of component I to component II is 1:0.05-0.5, preferably 1:0.1-0.3.
[0021] The second aspect of the present invention provides a method for preparing the above-mentioned wind power coating, comprising:
[0022] Step 1. Disperse rod-shaped titanium dioxide and cerium-containing soluble salt in a solvent, add a precipitant and mix, and then reflux, cool, dry and calcine in sequence to obtain a composite oxide, wherein Ce 3+ The content of cerium accounts for 25-35% by weight of the total cerium content;
[0023] Step 2. mixing the flake glass, the phenolic epoxy resin, the hydroxyl-terminated polyurethane resin and the antioxidant to obtain component I;
[0024] Step 3. Mix component I with component II, wherein component II is a curing agent.
[0025] On the basis of the above technical solution, the curing agent of component II comprises a mixture of an anhydride curing agent and a cationic curing agent.
[0026] On the basis of the above technical solution, the soluble salt containing cerium may be but is not limited to cerium nitrate, cerium sulfate and the like.
[0027] On the basis of the above technical solution, the solvent may be but is not limited to methanol, ethanol, water, etc.
[0028] On the basis of the above technical solution, the precipitant may be but is not limited to urea.
[0029] On the basis of the above technical solution, the reflux conditions include but are not limited to: temperature of 80-100° C. and time of 4-8 h.
[0030] Based on the above technical solution, the cooling conditions include: cooling to 20-25°C.
[0031] On the basis of the above technical solution, the drying conditions include but are not limited to: temperature of 100-120°C and time of 4-8h.
[0032] On the basis of the above technical solution, the calcination conditions include but are not limited to: temperature of 400-600° C. and time of 2-6 hours.
[0033] On the basis of the above technical solution, based on the total weight of the composite oxide, the content of rod-shaped titanium dioxide is 70-95% by weight, and the content of cerium oxide is 5-30% by weight.
[0034] The aspect ratio of the rod-shaped titanium dioxide is 2-10: 1. The aspect ratio of the rod-shaped titanium dioxide is, for example but not limited to, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc.
[0035] Based on the above technical solution, the thickness-to-diameter ratio of the flake glass is greater than 40 μm, preferably 70-90 μm.
[0036] Based on the above technical solution, the thickness of the flake glass is 3-7 μm.
[0037] Based on the above technical solution, the diameter of the flake glass is 40-150 μm. In the present invention, for the aspect ratio, thickness and diameter of the flake glass, within the above preferred range, the overall performance of the coating is better.
[0038] On the basis of the above technical solution, based on the total weight of the flake glass, the flake glass contains 50-80 weight % of SiO2, 5-10 weight % of Al2O3, 8-15 weight % of CaO, 2-8 weight % of MgO, 5-20 weight % of Na2O+K2O, and 0-0.5 weight % of Fe2O3.
[0039] On the basis of the above technical scheme, based on the total weight of component I, the content of flake glass is 30-40 weight%, the content of composite oxide is 5-20 weight%, the content of phenolic epoxy resin is 20-40 weight%, the content of hydroxyl-terminated polyurethane resin is 20-30 weight%, and the content of antioxidant is 5-10 weight%.
[0040] On the basis of the above technical solution, the phenolic epoxy resin may be but is not limited to phenolic epoxy resin F51.
[0041] On the basis of the above technical solution, the curing agent includes anhydride curing agent and a cationic curing agent.
[0042] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.
[0043] On the basis of the above technical solution, the cationic curing agent is selected from one or more of ammonium salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, boron trifluoride ether complex, etc.
[0044] On the basis of the above technical solution, based on the total weight of component II, the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6. The weight ratio of the anhydride curing agent to the cationic curing agent is, for example but not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6.
[0045] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.
[0046] On the basis of the above technical solution, the weight ratio of component I to component II is 1:0.05-0.5, preferably 1:0.1-0.3.
[0047] A third aspect of the present invention provides application of the above-mentioned wind power coating in the field of offshore wind power.
[0048] Beneficial effects of the present invention:
[0049] (1) In the present invention, Ce in the composite oxide 3+ When the content is controlled within the range of 25-35 weight % of the total cerium content, it is more beneficial to prevent the damage of salt water to the coating, and is more beneficial to the durability of the coating when used in offshore wind power.
[0050] (2) The crosslinking density of epoxy resin directly affects its physical and chemical properties, including hardness, strength, heat resistance and solvent resistance. High crosslinking density usually means better mechanical properties and thermal stability, but it may also cause the material to become brittle, which is particularly evident under extreme conditions such as cold and heat shock. The present invention introduces multi-functional polyurethane segments to balance the brittleness of epoxy resin through the flexibility of the polyurethane segments while maintaining sufficient crosslinking network density. The polyurethane segments themselves have good flexibility and elasticity, and can absorb and disperse energy when the epoxy resin is impacted by external forces, thereby effectively preventing the material from cracking or breaking. This toughening effect enables the modified epoxy resin to exhibit better durability and stability in harsh environments such as cold and heat, thereby improving the overall performance of the material.
[0051] (3) Anhydride curing agents are organic substances containing acid, and their acidity comes from the anhydride groups in their molecular structure. They can react with substances containing hydrogen atoms to initiate a curing reaction and form a strong and durable solid. Anhydride curing agents usually have low volatility and high activity. Coatings cured with anhydride curing agents usually have good weather resistance and chemical corrosion resistance, and can adapt to the complex weather conditions and chemical corrosion in the offshore wind power environment. Cationic curing agent is a new type of coating curing agent, which is non-toxic, odorless, solvent-free, environmentally friendly and will not pollute the environment. It has the characteristics of high strength, high hardness, wear resistance, chemical corrosion resistance and excellent weather resistance, and is a new high-tech product in the coating field. The heat and humidity resistance of epoxy resins obtained by curing with anhydride curing agents and cationic curing agents at the same time has unexpectedly improved. This is because anhydride curing agents cure epoxy resins according to a step-by-step polymerization mechanism, while cationic curing agents cure epoxy resins according to a chain polymerization mechanism. The combination of the two can form a more stable and heat-resistant coating structure. The offshore wind power environment is complex and changeable, and the performance requirements of coatings are high. The combined use of anhydride curing agent and cationic curing agent can improve the comprehensive performance of the coating and make it better adapted to the offshore wind power environment. However, the curing speeds of anhydride curing agent and cationic curing agent are different, so it is necessary to adjust the dosage ratio of the two. Prevent excessive use of a single component, resulting in degradation of epoxy resin performance. The ratio of the present invention, combined with other substances, can obtain a coating for offshore wind power with better performance. DETAILED DESCRIPTION
[0052] In the following technical description, for the sake of convenience of explanation, many details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details.
[0053] The terms "first", "second", etc. in the description and claims of the disclosed embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0054] The following are examples.
[0055] In the following examples, the raw materials were all purchased from commercial sources.
[0056] Preparation Example 1
[0057] Preparation of hydroxyl-terminated polyurethane resin:
[0058] 1000 parts by weight of dehydrated polytetrahydrofuran diol and 1 part by weight of dibutyltin dilaurate catalyst are added into the reactor, stirred and mixed, and nitrogen is introduced into the reactor for protection; the temperature is raised to 65°C, and 100 parts by weight of hexamethylene diisocyanate polyisocyanate is added, and the addition is controlled to be completed within 2 hours, and the temperature does not exceed 90°C; after the addition is completed, the internal temperature is maintained at 80-90°C for 3 hours; finally, a sample is taken, and the -NCO content is titrated by di-n-butylamine method. When the test result is 0, a hydroxyl-terminated polyurethane resin is obtained.
[0059] Example 1
[0060] Preparation of a wind power coating:
[0061] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0062] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0063] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide (obtained in step 1), 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0064] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0065] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0066] Example 2
[0067] A wind power coating is prepared according to the method of Example 1, except that the composite oxide is different, namely:
[0068] Step 1: Take 21 g of Ce(NO3)3·6H2O and 100 g of rod-shaped rutile (aspect ratio 8:1) and add them to 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0069] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 28% by weight of the total cerium content;
[0070] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0071] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0072] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0073] Example 3
[0074] A wind power coating is prepared according to the method of Example 1, except that component I is different, and the amounts of component I and component II are different, namely:
[0075] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0076] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0077] Step 3, 40g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 10g of a composite oxide, 25g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 5g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0078] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0079] Step 5: Mix 100 g of component I with 10 g of component II to obtain a wind power coating.
[0080] Example 4
[0081] A wind power coating is prepared according to the method of Example 1, except that component II is different, and the amounts of component I and component II are different, namely:
[0082] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0083] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0084] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0085] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 20 g of boron trifluoride ether complex to obtain component II;
[0086] Step 5: Mix 100 g of component I with 30 g of component II to obtain a wind power coating.
[0087] Example 5
[0088] A wind power coating is prepared according to the method of Example 1, except that component II is different, and the amounts of component I and component II are different, namely:
[0089] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0090] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0091] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0092] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 60 g of boron trifluoride ether complex to obtain component II;
[0093] Step 5: Mix 100 g of component I with 50 g of component II to obtain a wind power coating.
[0094] Example 6
[0095] A wind power coating is prepared according to the method of Example 1, except that component I is different, namely:
[0096] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0097] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0098] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 30g of a composite oxide, 15g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 5g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0099] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0100] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0101] Example 7
[0102] A wind power coating is prepared according to the method of Example 1, except that component I is different, namely:
[0103] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0104] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0105] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 3g of a composite oxide, 30g of a phenolic epoxy resin F51, 30g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 7g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0106] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0107] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0108] Example 8
[0109] A wind power coating is prepared according to the method of Example 1, except that component II is different, namely:
[0110] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0111] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0112] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0113] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 100 g of boron trifluoride ether complex to obtain component II;
[0114] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0115] Example 9
[0116] A wind power coating is prepared according to the method of Example 1, except that the amounts of component I and component II are different, namely:
[0117] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0118] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0119] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0120] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0121] Step 5: Mix 100 g of component I with 80 g of component II to obtain a wind power coating.
[0122] Comparative Example 1
[0123] A wind power coating is prepared according to the method of Example 1, except that the composite oxide is replaced by flake glass, that is:
[0124] Step 1, 45g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 20g of phenolic epoxy resin F51, 20g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0125] Step 2, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0126] Step 3: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0127] Comparative Example 2
[0128] A wind power coating is prepared according to the method of Example 1, except that the phenolic epoxy resin F51 is replaced with flake glass, that is:
[0129] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0130] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0131] Step 3, 50g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0132] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0133] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0134] Comparative Example 3
[0135] A wind power coating is prepared according to the method of Example 1, except that the hydroxyl-terminated polyurethane resin is replaced with flake glass, that is:
[0136] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0137] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0138] Step 3, 50g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0139] Step 4, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0140] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0141] Comparative Example 4
[0142] A wind power coating is prepared according to the method of Example 1, except that the boron trifluoride ether complex is replaced by a hexahydrophthalic anhydride curing agent, namely:
[0143] Step 1: Take 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1), add 720 mL of water, add 9 g of urea, stir well, and obtain a mixed solution;
[0144] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0145] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0146] Step 4, using hexahydrophthalic anhydride curing agent as component II;
[0147] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0148] Comparative Example 5
[0149] A wind power coating is prepared according to the method of Example 1, except that the hexahydrophthalic anhydride curing agent is replaced by a boron trifluoride ether complex, that is:
[0150] Step 1, add 27g of Ce(NO3)3·6H2O and 90g of rod-shaped rutile (aspect ratio 8:1) into 720mL of water, add 9g of urea, stir well, and obtain a mixed solution;
[0151] Step 2, the obtained mixed solution was transferred to a flask, heated to 80°C and refluxed for 4 hours, cooled to 25°C after the reflux was completed, the obtained reaction solution was centrifuged, the solid product was collected, dried at 110°C for 8 hours, and then placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a composite oxide; the Ce content of the composite oxide was obtained by XPS analysis and fitting. 3+ The content of cerium accounts for 32% by weight of the total cerium content;
[0152] Step 3, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of a composite oxide, 20g of a phenolic epoxy resin F51, 20g of a hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of an antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0153] Step 4, using boron trifluoride ether complex as component II;
[0154] Step 5: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0155] Comparative Example 6
[0156] A wind power coating was prepared according to the method of Example 1, except that only Ce(NO3)3·6H2O was mixed with rod-shaped rutile:
[0157] Step 1, 27 g of Ce(NO3)3·6H2O and 90 g of rod-shaped rutile (aspect ratio 8:1) were mixed to obtain a mixture;
[0158] Step 2, 30g of flake glass (with an aspect ratio of 80μm, a thickness of 5μm, and a diameter of 100μm), 15g of the mixture obtained in step 1, 20g of phenolic epoxy resin F51, 20g of hydroxyl-terminated polyurethane resin (obtained in Preparation Example 1), and 15g of antioxidant 168 are mixed to obtain component I; wherein, based on the total weight of the flake glass, the flake glass contains 69wt% of SiO2, 6wt% of Al2O3, 9wt% of CaO, 3.8wt% of MgO, 10wt% of Na2O, 2wt% of K2O, and 0.2wt% of Fe2O3;
[0159] Step 3, mixing 100 g of hexahydrophthalic anhydride curing agent and 40 g of boron trifluoride ether complex to obtain component II;
[0160] Step 4: Mix 100 g of component I with 20 g of component II to obtain a wind power coating.
[0161] Test Case
[0162] The wind power coatings of Examples 1-9 and Comparative Examples 1-6 were respectively tested for performance, and the drying time, adhesion, impact resistance, salt spray resistance, corrosion current density and corrosion potential were tested. The results are shown in Table 1.
[0163] (1) Drying time is tested according to GB / T 1728-2020 at a test temperature of 23±2℃.
[0164] (2) Adhesion was tested according to GB / T 5210-2006.
[0165] (3) Impact resistance is tested according to GB / T 1732-2020.
[0166] (4) Salt spray resistance is tested according to GB / T 1771-2007.
[0167] (5) Test method for corrosion current density and corrosion potential: The electrochemical properties of the coating were analyzed using an RST-3000 electrochemical workstation, with the coating obtained in the example or comparative example as the working electrode, a saturated calomel electrode as the reference electrode, Pt as the counter electrode, and a 3.5% NaCl solution as the medium.
[0168] Table 1
[0169]
[0170]
[0171] It can be seen from the above table that the wind power coating prepared by the formula of the present invention has the advantages of short drying time, strong adhesion, strong impact resistance, strong salt spray resistance, low corrosion current density and high corrosion potential.
[0172] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
[0173] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.
Claims
1. A wind power coating, comprising component I and component II; wherein component I comprises flake glass, composite oxide, phenolic epoxy resin, hydroxyl-terminated polyurethane resin and antioxidant, wherein the composite oxide comprises rod-shaped titanium dioxide and cerium oxide, and Ce in the composite oxide is 3+ The content of cerium accounts for 25-35% by weight of the total cerium content; the component II includes a curing agent.
2. The wind power coating according to claim 1, characterized in that: Based on the total weight of the composite oxide, the content of rod-shaped titanium dioxide is 70-95% by weight, and the content of cerium oxide is 5-30% by weight.
3. The wind power coating according to claim 1 or 2, characterized in that: The aspect ratio of the rod-shaped titanium dioxide is 2-10:
1.
4. The wind power coating according to any one of claims 1 to 3, characterized in that: The thickness-to-diameter ratio of the glass flake is greater than 40 μm, preferably 70-90 μm; and / or, The thickness of the flake glass is 3-7 μm; and / or, The diameter of the flake glass is 40-150 μm.
5. The wind power coating according to any one of claims 1 to 4, characterized in that: Based on the total weight of the flake glass, the flake glass contains 50-80 weight % of SiO2, 5-10 weight % of Al2O3, 8-15 weight % of CaO, 2-8 weight % of MgO, 5-20 weight % of Na2O+K2O, and 0-0.5 weight % of Fe2O3.
6. The wind power coating according to any one of claims 1 to 5, characterized in that: Based on the total weight of component I, the content of flake glass is 30-40 weight %, the content of composite oxide is 5-20 weight %, the content of phenolic epoxy resin is 20-40 weight %, the content of hydroxyl-terminated polyurethane resin is 20-30 weight %, and the content of antioxidant is 5-10 weight %.
7. The wind power coating according to any one of claims 1 to 6, characterized in that: The curing agent includes anhydride curing agent and cationic curing agent; Preferably, the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.
6.
8. The wind power coating according to any one of claims 1 to 7, characterized in that: The weight ratio of component I to component II is 1:0.05-0.5, preferably 1:0.1-0.
3.
9. The method for preparing the wind power coating according to any one of claims 1 to 8, comprising: Step 1. Dispersing rod-shaped titanium dioxide and cerium-containing soluble salt in a solvent, adding a precipitant and mixing, and then sequentially refluxing, cooling, drying and calcining to obtain a composite oxide; wherein Ce in the composite oxide is 3+ The content of cerium accounts for 25-35% by weight of the total cerium content; Step 2. mixing the flake glass, the phenolic epoxy resin, the hydroxyl-terminated polyurethane resin and the antioxidant to obtain component I; Step 3. mixing component I with component II, wherein component II is a curing agent; Preferably, the curing agent of component II comprises a mixture of an anhydride curing agent and a cationic curing agent. Preferably, the cerium-containing soluble salt is cerium nitrate and / or cerium sulfate; Preferably, the precipitating agent is urea; Preferably, the reflux conditions include: temperature of 80-100°C, time of 4-8h; Preferably, the drying conditions include: a temperature of 100-120°C and a time of 4-8h; Preferably, the calcination conditions include: a temperature of 400-600° C. and a time of 2-6 hours.
10. Application of the wind power coating according to any one of claims 1 to 8 in the field of offshore wind power.
Citation Information
Patent Citations
Packaging adhesive for LED, use method and application thereof
CN111826105A
Resin composition for LED with high humidity and heat resistance, preparation method of resin composition and LED packaging method
CN115851198A
Water-resistant catalyst as well as preparation method and application thereof
CN116422324A